2010
DOI: 10.1103/physrevb.81.155326
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous spin-related quantum phase in mesoscopic hole rings

Abstract: Anomalous spin-related quantum phase in mesoscopic hole rings. Physics, 81(15) We have obtained numerically exact results for the spin-related geometric quantum phases that arise in p-type semiconductor ring structures. The interplay between gate-controllable ͑Rashba͒ spin splitting and quantum-confinement-induced mixing between hole-spin states causes a much higher sensitivity of magnetoconductance oscillations to external parameters than previously expected. Our results imply a much-enhanced functionality of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…It also seems that in-plane fields in semiconductor devices such as the quantum rings, built on In-Ga-As structures, enables us to control the geometric phase of electrons [39]. In such devices, as the electron is transformed from the source to drain, the spin precession and the spin Berry phase of the electron are controllable by the Rashba coupling regulated by a perpendicular electric field [40][41][42]. Moreover, both of the Aharonov-Casher (AC) [43] and the Aharonov-Bohm (AB) [37] effects are experimentally and theoretically studied in quantum rings, which may be useful for controlling spin of electron [44].…”
Section: Introductionmentioning
confidence: 99%
“…It also seems that in-plane fields in semiconductor devices such as the quantum rings, built on In-Ga-As structures, enables us to control the geometric phase of electrons [39]. In such devices, as the electron is transformed from the source to drain, the spin precession and the spin Berry phase of the electron are controllable by the Rashba coupling regulated by a perpendicular electric field [40][41][42]. Moreover, both of the Aharonov-Casher (AC) [43] and the Aharonov-Bohm (AB) [37] effects are experimentally and theoretically studied in quantum rings, which may be useful for controlling spin of electron [44].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the spin-dependent transport experiments have demonstrated that it is possible to control the geometric phase of electrons by the application of in-plane fields in semiconductor devices such the quantum rings built on In-Ga-As structures [19]. In such devices, when an electron is transmitted from the source to drain, the spin precession and the spin-dependent phase (spin Berry phase) of the electron are controllable by the Rashba spin-orbit coupling, while this effect is regulated by a perpendicular electric field [20]. In addition, both the Aharonov-Bohm (AB) [17] and Aharonov-Casher (AC) [21] effects have been studied for quantum rings both experimentally and theoretically and may also be useful for controlling the spins of electrons [22].…”
Section: Introductionmentioning
confidence: 99%
“…20 Luttinger model taking heavy and light-hole states into account has recently been applied for the investigation of spin-related quantum phases. 21 For the theoretical description of transport properties of diametrically connected finite-width rings with Rashba SOI, a tight-binding model with concentric lattice of ring chains has been used 22 , while in Ref. [23] a spin-dependent recursive Green-function technique was applied to the relevant 2D Hamiltonian.…”
Section: Introductionmentioning
confidence: 99%